Balinese Local Wisdom's Perspective on Legal Protection for Children as Victims and Perpetrators of Sexual Abuse - Anak Agung Sagung Laksmi Dewi; Hartini Saripan; I Made Minggu Widyantara; Anak Agung Ngurah Adhi Wibisana (Jurnal Hukum Novelty, 2023)
Introduction to The Problem: The low quality of child protection based on the perspective of Positive Law in Indonesia has drawn much criticism from various elements of society who seem to prioritize the interests of victims compared to perpetrators of rape. Because without optimal protection, children will only become victims of a society that tends to be patriarchal. Therefore, the concept of restorative justice based on local wisdom is one of the solutions in legal protection for victims and children who commit sexual harassment towards minors who prioritize recovery.Purpose/Objective Study: This study aims to understand, explain, and analyze the existence of legal protection for victims and children who sexually abuse minors from the perspective of Balinese local wisdom.Design/Methodology/Approach: This article is the result of legal research, with statutory approaches, conceptual approaches, and case approaches. The types of legal materials used in this research are primary legal materials, secondary legal materials, and tertiary legal materials.Findings: Legal protection for children based on local wisdom is a form of settlement that can be used against children as victims and children as perpetrators referring to the provisions of Article 1 number 6 of Law No. 11 of 2012 concerning the Juvenile Criminal Justice System. The protection in question is the existence of traditional village institutions in Bali as an effort to protect children.Paper Type: Research Article